The Influence of Work Discipline on Employee Performance at the Berkat Kasih Imanuel Jakarta Foundation - Bawamenewi, Perina; Irawan, Pristanto Ria; Imanuddin, Kaffah; Fa’uzobihi, Fa’uzobihi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to determine the effect of work discipline on employee performance in Yayasan Berkat Imanuel Jakarta. This research uses quantitative descriptive methods with data collection techniques through distributing questionnaires and library data. This research uses saturated sampling with samples of 40 employees on Yayasan Berkat Imanuel Jakarta, using simple linear regression data analysis techniques. The results of this research show that there is an influence between work discipline on employee performance Yayasan Berkat Imanuel Jakarta is very influential and has an influential contribution of 78,5% on employee performance variables. It is hoped that the results of this research will contribute to further research.